TRAINING, WORK EXPERIENCE, AND COMPETENCY IN EMPLOYEE CAREER DEVELOPMENT AT KOPERASI SUBHAKTI UNGASAN - Purnama, I Kadek Agus Aldi; Tahu, Gregorius Paulus; Rismawan, Putu Agus Eka (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of training, work experience, and competence on employee career development at Koperasi Subhakti Ungasan, a rapidly growing organization in Bali. The background of this study is based on the importance of human resource development as a key factor in achieving organizational goals, particularly in terms of increasing motivation and performance. The research method used is quantitative with a saturated sampling technique involving 38 respondents. Data collection was conducted through observation, documentation, interviews, and online questionnaires, and analyzed using multiple linear regression. The results show that training, work experience, and competence each have a positive and significant effect on career development. These findings reinforce the goal setting and human resource management theories that emphasize the importance of clear goals, increasing individual capacity, and managing work relationships in creating competitive advantages. The limitations of training and the mismatch of competencies identified in cooperatives are important points for strategic improvement in the future.